Effect of Flow Rate NaOH on CO₂ Absorption Efficiency Using a Column Tray Absorber - Arifin, Rizal; Faizah, Nurul; Kaloka, Ardista Izdhihar; Aulia, Anisa Fatma; Thufailah, Gladys Sukma; Syukur, Muhammad Adnan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
CO₂ in industrial gas streams reduces process efficiency, corrodes equipment, and affects product quality. Additionally, CO₂ emissions contribute to climate change and global warming. To mitigate these effects, CO₂ removal through absorption is essential. Absorption involves contacting a gas mixture with a liquid absorbent to dissolve the gas component. This study examines the effect of CO₂ flow rate (V) and NaOH flow rate (L) on CO₂ absorption efficiency. The experiment involved preparing 33 liters of 0.1N NaOH and 250 ml of 0.1N HCl, followed by solution standardization using methyl orange. CO₂ was introduced through valve V-4 while NaOH was pumped into the absorption column. Samples were taken after steady state was reached, and titration with 0.1N HCl determined residual NaOH concentration. Flow rate variations of 1, 3, 5, 7, and 9 L/min were tested. Results align with literature, indicating that as CO₂ flow rate increases, NaOH flow rate also rises. However, the L/V ratio and absorbed CO₂ amount decrease due to reduced contact time, lowering absorption efficiency. This study highlights the importance of optimizing flow rates to enhance CO₂ capture.